Perspektif Maslahah Terhadap Pembagian Keuntungan Pada Unit Usaha Kelompok Usaha Tani Desa Wates Timur Pringsewu - Jayusman, Jayusman; Sari, Nova Puspita; Putra, Andi Eka; Bunyamin, Mahmudin (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this study is to find out the profit sharing from the collaboration between farmer groups and their administrators where the initial agreement at the East Wates Village Farmers Group business unit stated that all members would receive the same profit sharing every year. However, as time goes by, the distribution of profits is no longer the same as the original contract agreement. In practice, the management of the Farmer Group gets a higher profit share than ordinary members. The focus of the research is: how is Maslahah's review towards the profit sharing of farming business sales in the Farmer Groups of Wates Timur Pringsewu Village? The type of study is field research with descriptive-analytic. The primary data derives from the interviews and observations with administrators as well as the members of the East Wates Village Farming Group. Then the data was supplemented with secondary materials from library documents. The conclusion of this study is that the review of the Maslahah in terms of profit-sharing practices in Farmer Groups in East Wates Village does not bring benefits because there is an element of injustice. It violates the pillars of syirkah where the profits distributed to members are not in accordance with the agreement at the beginning. While the agreement is not immediately damaged or canceled because one of the pillars in the agreement is not implemented. It happens in accordance with a sense of justice due to administrators getting higher profits to match their responsibilities. Keywords: Farming Group, Maslahah, and Profit Sharing